Efficiency and safety of tranexamic acid in reducing blood loss in total shoulder arthroplasty: A systematic review and meta-analysis - Sun, Chuan-Xiu (Medicine (Baltimore), 2017)
OBJECTIVE: This meta-analysis aimed to evaluate the efficiency and safety of tranexamic acid for reducing blood loss and transfusion requirements in patients undergoing total shoulder arthroplasty. METHODS: A systematic search was performed in Embase (1980–2017.04, embase.com), Medline (1966–2017.04, medline.com), PubMed (1966–2017.04, pubmed.com), ScienceDirect (1985–2017.04, sciencedirect.com), and Web of Science (1950–2017.04, webofknowledge.com). Study which assessed the efficiency and safety of tranexamic acid in total shoulder arthroplasty was selected. Meta-analysis was performed using Stata 11.0 software. RESULTS: In all, 484 patients from 2 randomized controlled trials (RCTs) and 2 non-RCTs were subjected to meta-analysis. The present meta-analysis demonstrated that there was less total blood loss (mean difference [MD] −172.16, 95% confidence interval [CI] −35.46 to −308.87, P = .01, d = 0.33) and transfusion rate (odds ratio 0.34, 95% CI 0.13 to 0.91, P = .03, d = 0.29) in tranexamic acid groups compared with the control groups. There were no significant differences in duration of surgery (MD 0.02, 95% CI −0.12 to 0.22, P = .89, d = 0.19), length of stay (MD −0.06, 95% CI −0.26 to 0.14, P = .56, d = 0.20), or incidence of adverse effects such as deep venous thrombosis (odds ratio 1.15, 95% CI 0.33 to 4.00, P = .83, d = 0.53). CONCLUSION: Clinical application of tranexamic acid seemed to result in significant reductions in total blood loss, hemoglobin decline and transfusion requirements following total shoulder arthroplasty. Moreover, no increased risk of the thrombotic events was identified. Due to the limited quality of the evidence currently available, higher quality RCTs are required.